Carbon nanotube cement-based transducers for dynamic sensing of strain - Materazzi, Annibale Luigi; Ubertini, Filippo; D’Alessandro, Antonella (Cement & concrete composites, 2013)
A new type of sensor for structural health monitoring (SHM) has emerged since the birth and development of nanotechnology and is based on cementitious materials additioned with carbon nanoparticles that can provide measurable electrical responses to applied strain. The response of similar transducers was mainly investigated under slowly varying strains while applications in dynamics have not been yet documented. This paper is aimed at exploring the applicability of carbon nanotube–cement based sensors for measuring dynamically varying strain in concrete structures. Experiments are presented to investigate the electrical response of prismatic specimens made of carbon nanotube–cement composite when subjected to sinusoidal stress–strains in the typical frequency range of large civil structures. The results demonstrate that the sensors’ output retains all dynamic features of the input thus providing useful information for SHM and encouraging the transformation of structures into infinite sets of potential sensors with enhanced durability and limited access issues.